More than kings and less than men : Tocqueville on the promise and perils of democratic individualism - Hebert, L. Joseph (Louie Joseph), 1975- (Lexington Books, 2010)
This book explains why Tocqueville saw the central task of modern statesmanship as combating 'individualism, ' a type of civic apathy that he thought capable of robbing modern citizens of human virtue and issuing in a historically unprecedented form of despotism. It looks in depth at the mechanisms he proposed for avoiding the perils and securing the promise of democracy in his own day, and discusses how Tocqueville's insights might be applied in our own time.